Making the Transition from Conventional to Organic Farming Using Conservation Tillage in Florida - Tawainga W. Katsvairo; David L. Wright; Jim J. Marois; Pawel P. Wiatrak (EDIS)
Organic farming is one of the fastest-growing segments of agriculture in the U.S. and in Florida. Making the transition from conventional (strip till using genetically modified crops) to organic farming does not have to be filled with obstacles. National Organic Standards can be found on the National Organic Program web site at http://www.ams.usda.gov/nop. This document is SS-AGR-11, one of a series of the Agronomy Department, UF/IFAS Extension. Original publication date March 2006.